The State of the World’s Children 2024 - United Nations Children's Fund (United Nations, 2024)
The future is now. The carbon we pour into our atmosphere today will shape the climate of the future. The technologies we develop today – and the policies we develop to govern them – will help shape how we learn, work and communicate. They will affect the well-being of our children. The demographic trends of today will help shape the population patterns of societies tomorrow. So, the future is now – we are laying its foundations today. It is important that we ask ourselves: What will be in that future? What will the world be like for children in 2050? And what can we do today to ensure the best possible future for every child? These are the questions at the heart of this year’s The State of the World’s Children report. We cannot know for certain what the future holds. But we can examine the forces and trends shaping our world today and reflect on how they might shape the future. No list of these elements can be complete; after all, our world is complex, and so are the forces and trends shaping it. For example, in the years since the pandemic, a collision of political, social and economic trends has fuelled a global ‘polycrisis’ made up of intensifying challenges to democracy, fragmentation in the multilateral system and a debt crisis, which is “unsustainable and a recipe for social unrest”, according to United Nations Secretary-General António Guterres. Important commitments on many of these issues were made at the United Nations Summit of the Future in September 2024. The Pact for the Future, adopted at the Summit, states that the success of future generations is contingent on “eliminating the intergenerational transmission of poverty and hunger, inequality and injustice, and acknowledging the special challenges faced by the most vulnerable countries.”